An analysis of amplified insulin gene products in diabetics of Indian origin. Issue 2 (February 1991) - Hitman, G A; Kambo, P K; Viswanathan, M; Mohan, V
Abstract : We have previously described an increased incidence of the class 3 allele of the hypervariable region (HVR) 5' to the insulin gene in south Indian non-insulin dependent diabetics; this association is absent in Punjabi Sikhs with this disorder. Using the polymerase chain reaction we have amplified parts of the insulin gene from 130 subjects to look for mutations which may be in linkage disequilibrium with the class 3 allele and hence explain its association with non-insulin dependent diabetes (NIDDM). In 23 south Indian subjects with NIDDM, using the restriction enzyme MboII, a B chain mutant (insulin Chicago) was excluded. Two patterns (alpha and beta) were found, representing a PstI polymorphism in the 3' untranslated region of the insulin gene. In subjects homozygous for the class 1 allele, the allelic frequency for alpha was 0.94 (143/152) and for beta was 0.06, in heterozygotes (1, 3) alpha 0.63 (54/86) and beta 0.37, and in homozygotes for the class 3 allele alpha 0.18 (4/22) and beta 0.82 (p less than 0.001), thus establishing linkage disequilibrium between these two loci. No differences in allelic frequency were found in the south Indians or Punjabi Sikhs between controls and the different types of non-insulin requiring diabetes (NIDDM, fibrocalculous pancreatic diabetes and maturity onset diabetes of the young) when both groups were matched for insulin genotypes. Thus, although this polymorphism in the 3' untranslated region of the insulin gene is in linkage disequilibrium with the class 3 allele, it does not appear to be any better at predicting diabetes than the class 3 allele itself.